MiR-378a influences vascularization in skeletal muscles. Issue 7 (27th August 2019) - Krist, Bart; Podkalicka, Paulina; Mucha, Olga; Mendel, Mateusz; Sępioł, Aleksandra; Rusiecka, Olga Martyna; Józefczuk, Ewelina; Bukowska-Strakova, Karolina; Grochot-Przęczek, Anna; Tomczyk, Mateusz; Klóska, Damian; Giacca, Mauro; et al.
Abstract: Aims: MicroRNA-378a, highly expressed in skeletal muscles, was demonstrated to affect myoblasts differentiation and to promote tumour angiogenesis. We hypothesized that miR-378a could play a pro-angiogenic role in skeletal muscle and may be involved in regeneration after ischaemic injury in mice. Methods and results: Silencing of miR-378a in murine C2C12 myoblasts did not affect differentiation but impaired their secretory angiogenic potential towards endothelial cells. miR-378a knockout (miR-378a−/−) in mice resulted in a decreased number of CD31-positive blood vessels and arterioles in gastrocnemius muscle. In addition, diminished endothelial sprouting from miR-378a−/− aortic rings was shown. Interestingly, although fibroblast growth factor 1 ( Fgf1 ) expression was decreased in miR-378a−/− muscles, this growth factor did not mediate the angiogenic effects exerted by miR-378a. In vivo, miR-378a knockout did not affect the revascularization of the ischaemic muscles in both normo- and hyperglycaemic mice subjected to femoral artery ligation (FAL). No difference in regenerating muscle fibres was detected between miR-378a−/− and miR-378+/+ mice. miR-378a expression temporarily declined in ischaemic skeletal muscles of miR-378+/+ mice already on Day 3 after FAL. At the same time, in the plasma, the level of miR-378a-3p was enhanced. Similar elevation of miR-378a-3p was reported in the plasma of patients with intermittent claudication in comparison to healthy donors. Local adeno-associated viral vectors-based miR-378a overexpression was enough to improve the revascularization of the ischaemic limb of wild-type mice on Day 7 after FAL, what was not reported after systemic delivery of vectors. In addition, the number of infiltrating CD45 + cells and macrophages (CD45+ CD11b+ F4/80+ Ly6G−) was higher in the ischaemic muscles of miR-378a−/− mice, suggesting an anti-inflammatory action of miR-378a. Conclusions: Data indicate miR-378a role in the pro-angiogenic effect of myoblasts and vascularization of skeletal muscle. After the ischaemic insult, the anti-angiogenic effect of miR-378a deficiency might be compensated by enhanced inflammation. Graphical Abstract: